Investigation on the mechanical stresses in a muffler mounting bracket using Root Cause Failure Analysis (RCFA), finite element analysis and experimental validation. (November 2017) - Dondapati, Sreekanth; Trivedi, Mudit; Dondapati, Raja Sekhar; Chandra, Divya
Abstract: In the present work, experimental investigation on the failure of a muffler mounting bracket attached to commercial vehicle is done. Cracks are identified at the welded location of muffler mount which shows that weld joint has better strength than the muffler/bracket body. To understand the possible root causes of the failure, fishbone diagram was used, which helped in determining the major causes of the failure by a graphical representation. Further, the three parameter Weibull distribution was also developed to determine the Mean Time to Failure (MTTF) life which was found to be 15, 172 km. In addition, tensile testing of sheet metal was performed on the sheets which was used in the manufacturing of Muffler. Furthermore, a Thermo-Mechanical coupled analysis was carried out using commercial code, ANSYS 16.0, which adapts Finite Element Analysis (FEA) formulation. The thermal loads on muffler were imported to structural analysis along with a static load of 4 g acceleration were imposed on the muffler body to simulate the effects of high impact loads. The effect of temperatures resulted in high von-misses stresses which were in agreement with practical observations. It is observed that the stresses at bracket region were at the same location both from the experimental and finite element analysis. Further, by considering different mounting design concepts, multiple analyses were carried out to determine the most suitable brackets for the muffler. The present work attempts to diagnose the cause of failure and to make the fail-safe design. Highlights: The possible root cause of the failure couldn't be identified with the help of RCFA study due to insufficient data available. Statistical distribution helps to study the life cycle of the component. FEA has been very helpful in terms of modifying design, comparing different designs for the current studies.